Experimental Substantiation of Therapeutic Hypothermia and Cell Therapy Application at Dyscirculatory Encephalopathy in SHR Rats. Part 2. Structural Changes in Brain Tissue - Aidarova, Viktoria S.; Babiichuk, Vladislav G.; Kudokotseva, Olga V.; Naumova, Olga V.; Lomakin, Ivan I.; Protsenko, Olena S. (Problems of Cryobiology and Cryomedicine, 2019)
Nowadays the cerebral vascular diseases are recognized as the main causes of disability and mortality, and the issues of optimizing the pathogenetic therapy of this disease remain far from being solved. In this regard, the development of new effective methods to combat the development and progression of cerebrovascular disorders in dyscirculatory encephalopathy (DE) is the most important task of medicine and biology. In this paper, we evaluated the morphological and morphometric parameters of brain tissue in the SHR rats 30 days after applying the rhythmic craniocerebral hypothermia and cryopreserved cord blood nucleated cells. It has been shown that each of the studied methods of influence has a more or less positive effect on reducing the severity of degeneration in the tissue of rat’s brain with the DE signs. The combined use of these methods contributed to their mutual potentiation, manifested in a decrease in the degree of degenerative-dystrophic lesions of brain tissue, as evidenced by a significant decrease in the neuroglial index. Probl Cryobiol Cryomed 2019; 29(1): 058–072